Price Comparison of Moringa in the Greater District of Columbia Area, United States of America - Lillian Onokala; Garrard Baker; Bisrat Hailemeskel (Advances in Food Technology and Nutrition Sciences, 2022)
Introduction Moringa oleifera (MO) is a nutritional herbal supplement that grows in many subtropical and tropical regions of the world including India, Africa, North and South America, and Asia. The purpose of this study is to review recent clinical studies regarding the health benefits of MO as well as investigate the availability and relative pricing of MO among retail local and online stores for the various Moringa dosage forms. MethodIn this study, price variations and availability of MO in 18 retail companies that serve the District of Columbia, Maryland, and Virginia region were investigated. Price comparisons of the three major formulations of MO-powder, capsules, and tea-were performed through store-to-store and online searches. Results This investigation on retail selling pricing of Moringa has shown that Moringa is a very affordable and accessible product in the greater District of Columbia, Maryland, Virginia region. However, we found a major gap and range in prices among the dosage forms and among the 18 stores included in our study. The average selling price per day for all dosage forms is 0.39, ranging from 0.31 to 0.55. The powder is the most commonly carried dosage form of the supplement, and also has the greatest variation in pricing among the stores. In addition, it was noted that the capsule is the most expensive dosage form (0.55 vs. 0.31 for the pow-der and tea forms) for daily dosing. A comparison of cost per gram per day dosing was done and shows that there are significant differences in the selling price among the three dosage forms with a p-value of less than 0.05. Discussion MO has many health benefits and is an excellent value as a nutritional supplement. Numerous studies have shown Moringa to have excellent anti-inflammatory, antioxidant, and antimicrobial activity. In the evaluation of dosage price per day, it was found that for over half of the stores (56%; n=16) the Moringa powder was under 0.50, while for three-fourths of the stores (75%; n=12) it was under 1.00. Moringa is readily available in most stores. Over two-thirds (67%; n=11) of the stores carry all three dosage forms. However, there is a major gap range in the price per day and the daily dose quantity of the herb for each dosage form. The powder dosage form was found to be the most readily available form of the supplement and the least expensive. Conclusion It was found that Moringa is relatively inexpensive and is a great value for the health benefits obtained. The powder dosage form is the most readily available form while the capsule is the most expensive dosage form. It is important to emphasize in pharmacist counseling sessions that patients should shop around and compare prices when choosing their desired Moringa product.